Implementasi Peraturan Kejaksaan Republik Indonesia Nomor 15 Tahun 2020 (Studi Kasus Di Kejaksaan Negeri Jembrana) - Antonius De Andrade Fahik; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2022)
Settlement of criminal cases within the framework of the criminal justice system in Indonesia always leads to the imposition of imprisonment or corporal punishment as a form of deterrent effect to perpetrators of criminal acts as the implementation of the articles in the Criminal Code which still uses the theory of punishment, namely the theory of purpose or theory. relatively. The purpose of the research is to reveal the implementation of the Republic of Indonesia Prosecutor's Regulation No. 15 of 2020 (a case study at the Jembrana District Attorney's Office). The research method used in this research is an empirical research method with a case research approach. This research uses primary and secondary data sources. Data were analyzed using qualitative analysis methods. The results of this research indicate that the role of law enforcement officers in particular the role of the prosecutor's office in resolving a criminal case using a restorative justice approach must be carried out massively and comprehensively, in order to meet the demands of justice oriented towards justice in society.